COMPLEXITY OF THE TUBERCULOSIS CHAIN IN EXTENDED FAMILIES WITH COLLECTIVIST CULTURE: A CASE REPORT (Proceedings of the International Conference of Community Health and Medical Sciences, 2024)
Indonesia is a country with the second rank of new tuberculosis cases in the world. One of Indonesia cultural that is collectivist culture, which is one of its characteristics, is gathering in a large family (extended family) in one house can pose a risk of spreading infectious diseases such as tuberculosis. The purpose of this report was to analyze tuberculosis cases with family medicine approach. The method used a holistic examination, namely anamnesis, observation and examination using a family medicine approach (genogram, Family APGAR and SCREEM, also home environment). The location took place at Gatak Primary Health Care, Sukoharjo Regency, Province of Central Java, Indonesia in June 2023. The result, we examined a 7-month-old girl and it was found that other family members also had tuberculosis (grandparents had a history of tuberculosis with completed treatment, the patient cousin was being treated at a type A hospital). The patient home environment was usually exposed to cigarette smoke. The patient lived in a house with a family consisting of 4 generations (extended family). APGAR Family showed very functional. SCREEM Family showed that the house was often used as a meeting place for residents and the illness was not shared because it was still a taboo subject. The family was good in formal education and there was health workers in family members, but it was a bad habit that if a family member was sick, the house would be the place to take care of them. The home environment had lack in sanitation hygiene. Conclusion: The management of each patient can be different, to achieve disease eradication we cannot just give therapy without taking a family approach.
Keywords: collectivist culture; tuberculosis; extended family